The Effect of Think Pair Share Learning Model on Junior High School Students' Response Text Writing Skills - Pradyta, Septiana; Harahap, Rosmawaty (UIR Press, 2024)
The problem of learning to write response texts that could be more optimal is due to inappropriate learning models. This is the background of this research. This research examines how the implementation model of Think Pair Share learning helps junior high school students improve their skills in composing response texts. The method used in this research is an experimental method with a group posttest-only control design. A total of 186 students enrolled in grade IX of Junior High School 41 Medan constituted the population in this study. This study involved 28 students from class IX-2 and 28 from class IX-4 as samples. This study used quantitative data analysis using homogeneity, normality, and hypothesis tests. The results prove that without the Think Pair Share learning model, the average skill of composing student response text is below the minimum completeness criteria score of 75, with an average score of 66.07. For students who apply the Think Pair Share learning model, the average student score for writing response text is 85.85. The result represent that it can be concluded that students who apply the Think Pair Share learning model get a more excellent value than those who do not. Hypothesis testing shows that tcount > ttable, or 6.18 > 2.04. This indicates that the Think Pair Share learning model significantly affects the skills of junior high school students composing response texts. This research aims to provide information to academic and educational institutions about how the Think Pair Share learning model influences the skills of composing response texts of junior high school students.